2010
DOI: 10.1103/physreva.82.023807
|View full text |Cite
|
Sign up to set email alerts
|

Self-pulsations and excitability in optically injected quantum-dot lasers: Impact of the excited states and spontaneous emission noise

Abstract: International audienceWe study the dynamics of an optically injected quantum-dot laser accounting for excited states. Mapping of the bifurcations in the plane frequency detuning vs. injection strength shows that the relaxation rate scales the regions of locking and single- and double-period solutions, while the capture rate has a minor effect. Within the regions of time-periodic solutions, close to the saddle-node bifurcation boundary, we identify subregions where the output signal resembles excitable pulses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Time traces of the total power shown in Figs. 4(f) and 4(h) resemble the traces showing single-pulse excitability or self-pulsating behavior observed in [23,24]. …”
Section: Experimental Results: Small Bias Currentmentioning
confidence: 53%
See 1 more Smart Citation
“…Time traces of the total power shown in Figs. 4(f) and 4(h) resemble the traces showing single-pulse excitability or self-pulsating behavior observed in [23,24]. …”
Section: Experimental Results: Small Bias Currentmentioning
confidence: 53%
“…Theoretical calculations in VCSELs subject to orthogonal optical injection predicted that the two linearly polarized modes are anticorrelated at the time scale of slow oscillations while they exhibit an in-phase dynamics at the fast time scale of the relaxation oscillations [22]. Very recently, excitability and self-pulsating dynamics has been analyzed in optically injected quantum-dot and quantum-well laser diodes [23,24]. Time traces of the total power shown in Figs.…”
Section: Experimental Results: Small Bias Currentmentioning
confidence: 99%
“…Recently some of us demonstrated that the characteristics of the first excited state (lasing or not) can have a major impact on the dynamics of optically injected QD lasers [20], [21]. Indeed the intraband relaxation time from the ES to the GS can enlarge or reduce the locking region, modifying the excitability characteristics of the system [6].…”
Section: Introductionmentioning
confidence: 98%
“…The fast non-Arrhenius character of the ISI originates in a noise-induced diffusion through both branches of the stable manifold, thus initiating another excursion in phase space before relaxing to the CW state. Such a noise clustering of pulses due to the proximity of the relaxation trajectory of the excited pulse and the excitability threshold has been observed in several other noise-driven excitable systems, such as lasers with optical feedback [24,25], quantum-dot lasers with optical injection [28,40], and neurons of the Hodgkin-Huxley type [41].…”
Section: B Interspike-interval Diagrammentioning
confidence: 69%